The Language of Soccer – a Sociolect or a Register? - Lewandowski, Marcin (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2008)
The theoretical framework of this paper is based upon the views of Polish and Anglo-Saxon sociolinguists on the concepts of sociolect and register. In the main section the author gives a brief overview of the language of soccer and distinguishes 10 subvarieties of this language, which differ from each other mainly in lexico-grammatical as well as stylistic features. Finally, the author attempts to categorize each of these subvarieties as either a sociolect or a register.

Abstrakt (Język piłki nożnej – socjolekt czy rejestr?). Podstawę teoretyczną rozważań w niniejszym artykule stanowią poglądy polskich i anglosaskich socjolingwistów dotyczące pojęć socjolektu i rejestru. W zasadniczej części tekstu autor charakteryzuje pokrótce język piłki nożnej, wyróżniając 10 pododmian tego języka, które różnią się między sobą głównie pod względem leksykalno-gramatycznym, jak również stylistycznym. Na koniec zostaje podjęta próba zaszeregowania każdej z omówionych pododmian do grupy socjolektów bądź rejestrów.
Keywords: Language of soccer; Sociolect; Register; Socioliguistics